Illness representations of chronic obstructive pulmonary disease (COPD) to inform health education strategies and research design—learning from rural Uganda. Issue 4 (23rd July 2020) - Nagourney, Emily M; Robertson, Nicole M; Rykiel, Natalie; Siddharthan, Trishul; Alupo, Patricia; Encarnacion, Marysol; Kirenga, Bruce J; Kalyesubula, Robert; Quaderi, Shumonta A; Hurst, John R; Checkley, William; Pollard, Suzanne L; et al.
Abstract: More than 90% of chronic obstructive pulmonary disease (COPD)-related deaths occur in low- and middle-income countries; however, few studies have examined the illness experiences of individuals living with and providing treatment for COPD in these settings. This study characterizes illness representations for COPD in Nakaseke, Uganda from the perspectives of health care providers, village health teams and community members (CMs) with COPD. We conducted 40 in-depth, semi-structured interviews (16 health care providers, 12 village health teams and 12 CMs, aged 25–80 years). Interviews were analyzed using inductive coding, and the Illness Representations Model guided our analysis. Stakeholder groups showed concordance in identifying causal mechanisms of COPD, but showed disagreement in reasons for care seeking behaviors and treatment preferences. CMs did not use a distinct label to differentiate COPD from other respiratory illnesses, and described both the physical and social consequences of COPD. Local representations can inform development of adapted educational and self-management tools for COPD.